2009
DOI: 10.1111/j.1365-2583.2009.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression during compensatory sprouting of dendrites in the auditory system of the cricketGryllus bimaculatus

Abstract: Neurons that lose their pre-synaptic partners due to injury usually retract or die. However, when the auditory interneurons of the cricket are denervated, dendrites respond by growing across the midline and forming novel synapses with the opposite auditory afferents. Suppression subtractive hybridization was used to detect transcriptional changes three days after denervation. This is a stage at which we demonstrate robust compensatory dendritic sprouting. While 49 unique candidates were downregulated, no suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 71 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…Presumably, the axons and dendrites contralateral to deafferentation were affected indirectly or secondarily by the unilateral loss of auditory input. All of these novel results define parameters of deafferentation-induced growth that must be taken into account as we search for the molecular cues which induce or facilitate these morphological changes [Horch et al, 2009]. As a preliminary step in this search, we have also shown that vamp and sema2a are differentially regulated upon deafferentation, indicating that transcriptional changes in well-conserved genes may play a role in the anatomical changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Presumably, the axons and dendrites contralateral to deafferentation were affected indirectly or secondarily by the unilateral loss of auditory input. All of these novel results define parameters of deafferentation-induced growth that must be taken into account as we search for the molecular cues which induce or facilitate these morphological changes [Horch et al, 2009]. As a preliminary step in this search, we have also shown that vamp and sema2a are differentially regulated upon deafferentation, indicating that transcriptional changes in well-conserved genes may play a role in the anatomical changes.…”
Section: Discussionmentioning
confidence: 99%
“…Deafferentation in a number of organisms has been shown to regulate the transcriptional level of individual or even dozens of different genes [Kwak and Matus, 1988;Mostafapour et al, 2002;Harris et al, 2005;Wang et al, 2005;Schäfer et al, 2008;Wang and Rubel, 2008;Horch et al, 2009]. Discussion of the candidates that may influence this process in crickets is, out of necessity, still speculative since the genome of G. bimaculatus has not yet been sequenced.…”
Section: Implications For Molecular Control Of Compensatory Sproutingmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid evolution of singing behaviour on the Hawaiian archipelago under the pressure of flies hearing the cricket song and preying on crickets is a fascinating example (Zuk et al 2006). There are advances in molecular approaches as well; regeneration and plasticity in the cricket auditory system can now be studied at the molecular level (Horch et al 2009) and in 2015 the first genetic knockout crickets have been developed with recent genome editing techniques (Awata et al 2015). The fast developments in this field are promising.…”
mentioning
confidence: 99%